Learning about volunteering: an exploration of literacy volunteers' experiences - Yendall, Kaitlin Amy (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
After almost 25 years of democracy in South Africa, not everyone has access to the same quality education. The responsibility of creating a literate society however cannot rely on the national government and schools alone, but instead needs to fall on the shoulders of various stakeholders. Volunteers in particular have an important role to play in remedying the current literacy crisis experienced in South Africa. This study takes the form of a case study approach and examines the experiences of Project Read literacy volunteers. A telephonic survey and two focus group discussions were conducted in order to determine who it is that volunteers for the programme; what prompts these particular individuals to volunteer; the perceived benefits of volunteering; and how volunteers report on their volunteering experiences. Although the Project Read programme is focused on the early literacy development of learners, volunteers seemed to undergo a developmental process themselves "“ something they had not anticipated at the start of their volunteering journey. This study illustrates the power of meaningful relationships in breaking down artificial categories and in bringing about important change with regards to the perceptions and attitudes of individuals towards community engagement. It is hoped that the data generated through this study will assist in recruiting and retaining more literacy volunteers through feedback to the NGO. In this way more children will be assisted to enhance their literacy competencies, from which they can build and achieve.
Keywords: Literacy -- Study and teaching -- South Africa; Literacy programs -- South Africa; Voluntarism -- South Africa; Volunteer workers in community development -- Training of; Service learning; Language and education -- South Africa; Language arts (Primary); English language -- Study and teaching (Elementary); Volunteer workers in Education -- Training of